Balloon Angioplasty vs. Stenting for Symptomatic Intracranial Arterial Stenosis - Sun, Yaxuan; Li, Xihua; Ding, Yongxia; Han, Bin; Wang, Jing; Meng, Kun; Han, Yan (Frontiers in Neurology, 2022)
Aims We performed a meta-analysis to indirectly compare the treatment effectiveness of balloon angioplasty and stenting for patients with intracranial arterial stenosis. Methods Literature searches were performed in well-known databases to identify eligible studies published before January 04, 2021. The incidence of restenosis, transient ischemic attack (TIA), stroke, death, and dissection after balloon angioplasty or stenting were pooled. An indirect comparison of balloon angioplasty vs. stenting was performed, and the ratios of incidence (RIs) with 95% confidence intervals (CIs) were calculated using the random-effects model. Results 120 studies that recruited 10,107 patients with intracranial arterial stenosis were included. The pooled incidence of restenosis after balloon angioplasty and stenting were 13% (95%CI: 8-17%) and 11% (95%CI: 9-13%), respectively, with no significant difference between them (RI: 1.18; 95%CI: 0.78–1.80; P = 0.435). Moreover, the pooled incidence of TIA after balloon angioplasty and stenting was 3% (95%CI: 0–6%) and 4% (95%CI: 3%-5%), and no significant difference was observed (RI: 0.75; 95%CI: 0.01–58.53; P = 0.897). The pooled incidence of stroke after balloon angioplasty and stenting was 7% (95%CI: 5–9%) and 8% (95%CI: 7–9%), respectively, and the difference between groups was found to be statistically insignificant (RI: 0.88; 95%CI: 0.64–1.20; P = 0.413). Additionally, the pooled incidence of death after balloon angioplasty and stenting was 2% (95%CI: 1–4%) and 2% (95%CI: 1–2%), with no significant difference between groups (RI: 1.00; 95%CI: 0.44–2.27; P = 1.000). Finally, the pooled incidence of dissection after balloon angioplasty and stenting was 13% (95%CI: 5–22%) and 3% (95%CI: 2–5%), respectively, and balloon angioplasty was associated with a higher risk of dissection than that with stenting for patients with intracranial arterial stenosis (RI: 4.33; 95%CI: 1.81–10.35; P = 0.001). Conclusion This study found that the treatment effectiveness of balloon angioplasty and stenting were similar for patients with symptomatic intracranial arterial stenosis.